Differing approaches to public space and the multicultural in the (re)making of a strategic place: Mouraria in Lisbon, Portugal (2007-present) - Gomes, Pedro (2014)
Lisbon’s mayoral team elected in 2007 set the attraction of new residents and employment and the enhancement of the city’s quality of life as its main objectives. Urban rehabilitation and public spaces soon emerged as two cornerstones in attaining such goals. The regeneration of Mouraria would become one of the Office’s flagship projects. Mouraria is a historical neighbourhood standing between the city centre and some of Lisbon’s major tourist attractions, whose development was hampered by physical dereliction, social deprivation and widespread negative representations as a site of crime and deviance. Aiming at attracting new residents, activities and boosting the neighbourhood’s touristic appeal, the council set a program of major urban regeneration in motion, heavily reliant on public space requalification. The program was soon to be accompanied by myriad initiatives spearheaded by the city council and involving different local stakeholders. These multiple initiatives mobilize differently two of the neighbourhood’s most distinguishing identity traits: its large immigrant population; and its being the “authentic” lisboetas, the cradle of fado music. This paper focuses on three of these public space initiatives: the urban regeneration program and its “social” counterpart; Todos, a festival celebrating the neighbourhood’s cultural diversity; and Mercado de Fusão, the concept behind the private management of Mouraria’s main square. Drawing on official documents, press clippings and several interviews with municipal technicians and local stakeholders, I discuss the different visions of the public as a noun and subject of urban policy present in each of these instances, and the ways cultural identity and diversity are engaged with. In so doing, I hope to demonstrate how an understanding of current change in Mouraria can benefit from an analysis of the different rationalities at play, thereby mitigating overgeneralizing political economy accounts and monolithic views of the public institution as an urban stakeholder.